A coumarin-based fluorescent probe for the fast detection of Pd0 with low detection limit. Issue 13 (30th March 2016) - Liu, Yunchang; Xiang, Kaiqiang; Guo, Min; Tian, Baozhu; Zhang, Jinlong
Graphical abstract: We design a fluorescent probe for the detection of palladium with the high sensitivity and selectivity. The probe shows nonfluorescence when connected with allyl carbonate ester which destroys the ICT system. The effect of palladium to the probe can change the structure. As a result, the fluorophore is exposed and it shows fluorescence. Highlights: A coumarin-based fluorescent probe for the detection of Pd 0 is designed and synthesized. The probe shows good selectivity towards Pd 0 compared with many other ions. The probe can detect Pd 0 even with the disturbance of quantity of other metal ions. The detection limit is as low as 0.34 nM which is lower than the specific threshold in drugs. Abstract: A off–on coumarin-based fluorescent probe for the fast detection of Pd 0 is designed and synthesized. The probe shows not only good selectivity but also fast response to Pd 0 in phosphate buffered saline (PBS) solution. The absorption band at 412 nm rises sharply as well as the fluorescence at 450 nm after the addition of Pd 0 within few minutes. The detection limit is as low as 0.34 nM. The probe shows nonfluorescence when it conjuncted with allyl carbonate ester which destroys the Intramolecular Charge Transfer (ICT) system. The effect of Pd 0 to the probe can change the structure and make the departure of the conjuncted allyl carbonate ester. As a result, the fluorogen is exposed and it shows fluorescence.